2021
DOI: 10.3390/plants10030501
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Chemical Composition and Antioxidant Activity of Essential Oils and Crude Extracts of Four Characteristic Zingiberaceae Herbs

Abstract: The ginger family (Zingiberaceae) includes plants that are known worldwide to have a distinctive smell and taste, which are often used as spices in the kitchen, but also in various industries (pharmaceutical, medical, and cosmetic) due to their proven biological activity. The aim of this study was to investigate and compare the chemical composition and antioxidant activity (AA) of essential oils (EOs) of four characteristic ginger species: Elettaria cardamomum L. Maton (cardamom), Curcuma Longa L. (turmeric), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 72 publications
(79 reference statements)
3
46
0
Order By: Relevance
“…In C. longa, β-turmerone, α-turmerone, Ar-turmerone, 16-kauren-19-yl acetate, α-atlantone, β-sesquiphellandrene, and benzene were identified (Figure 1b). The compounds identified in both aqueous extracts represent the bioactive compounds previously reported for both plants [11].…”
Section: Compound Identificationsupporting
confidence: 58%
See 2 more Smart Citations
“…In C. longa, β-turmerone, α-turmerone, Ar-turmerone, 16-kauren-19-yl acetate, α-atlantone, β-sesquiphellandrene, and benzene were identified (Figure 1b). The compounds identified in both aqueous extracts represent the bioactive compounds previously reported for both plants [11].…”
Section: Compound Identificationsupporting
confidence: 58%
“…The following phytochemical tests were performed to identify the functional groups of each extract: Lieberman-Buchard (sterols, triterpenes), Shinoda (flavonoids), Baljet (sesquiterpene lactones), sulfuric acid (quinones), and ferric chloride (tannins) [19], then each extract was analyzed by gas chromatography coupled to GC/MS mass for identification of the main components of its chemical composition [11].…”
Section: Qualitative Phytochemical Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown the efficacy of docking studies to identify the potential amino acid sites in enzyme as potential sites for drug development [40,41]. It was also validated that there might be some variation in the pharmacological properties of plant extracts depending upon the solvent system adopted for extraction [42].…”
Section: Discussionmentioning
confidence: 97%
“…The ethanol extracts of S. involucratus had anti-inflammatory, antinociceptive, and antipyretic activities [ 4 , 5 ]. The extraction of Elettaria cardamomum , Curcuma longa , Zingiber officinale , and Alpinia officinarum had the scavenging activity of the cationic ABTS radical and ferric-reducing antioxidant power-FRAP [ 6 ]. The standardized extraction from the rhizomes of ginger defended a rat liver from cancer by decreasing oxidative and inflammatory injury [ 7 ].…”
Section: Introductionmentioning
confidence: 99%